Narratives of how young men raised in lesbian and gay families navigate South African Heteronormativities - Matabane, Bongani Samuel (University of Cape Town, 2023)
South Africa is currently the only country in the continent to fully legally recognise same-sex marriage. While this is a post-apartheid nationalism feat that needs and should be celebrated, those who live openly as gay/lesbian continue to be despised by a large portion of the population (Gouws, 2005). There is an overwhelming body of research in the continent, including South Africa, that focuses on the narratives of homophobia and violence experienced by gay/lesbian individuals (see Mkhize, Bennett, Reddy & Moletsane, 2010; Judge, 2018). Despite the growing visibility of gay/lesbian headed families in the country, little is known about children raised in such families. Existing literature often focuses on the impact homosexuality has on children from the perspective of the gay/lesbian parents while ignoring the importance of giving a voice to children who come from such families. Using a qualitative approach, this study explored narratives of how young men raised in gay/lesbian families navigate heteronormative communities in South Africa. Queer theory and theory on Radical Democracy were adopted as theoretical frameworks while the data was produced through semi-structured interviews conducted in person and virtually with eight men raised in gay/lesbian families. Themes and sub-themes emerged through a narrative thematic analysis, highlighting the intricacies and tensions in how these men navigate heteronormative environments. Constructing narratives about (counter)heteronormative environments, encounters of disclosure, self-identification narratives, and growing up as a boy/man in counter-heteronormative families were the themes that arose from their narratives. Their narratives revealed that there is no such thing as a universal moment of disclosure and that ‘coming out' is a complex family process that sometimes occurs in the context of divorce and parental conflict and that sometimes, ‘coming out' was irrelevant for these men because the narrative of disclosure was not allowed. The men learned to represent a positive alternative masculinity that challenges mainstream sexist ideas of women and girls as objects as a result of growing up in counter-heteronormative families. The research suggests that living ‘the laws of democracy' within intimate family settings is a complex and multidetermined business, demanding both continuous vigilance around wide-spread homophobia and attunement to new modes of masculinity formation in the country.